Postgrowth nondestructive characterization of dilute-nitride VCSELs using electroreflectance spectroscopy - Choulis, Stelios A.; Hosea, Thomas Jeff Cockburn; Ghosh, Sandip Kumar (My University, 2003)
We report electroreflectance (ER) measurements on a dilute-N GaInNAs vertical-cavity surface-emitting laser structure, as a function of temperature T, which probe the coupling between the cavity mode (CM) and a broad quantum-well (QW) ground state exciton. The latter is not separately observable in the ER, but, by monitoring the coupled CM-QW lineshape, we show it has maximum amplitude and is anti-symmetric when the CM and QW energies coincide at a certain T/sub opt/. This predicted T/sub opt/ is confirmed by optically pumped lasing measurements on the same sample
Keywords: Optical pumping; Erbium; Spectroscopy; Gallium arsenide; Indium compounds